Single-Anastomosis Plication Ileal Bypass (SAPI) in Treatment of Morbid Obesity. Issue 2 (April 2019) - Elbanna, Hosam; Emile, Sameh; Abdel-Razik, Mohamed A.
Abstract : Background: This report aimed to demonstrate the technical steps and preliminary outcome of a novel bariatric procedure, the single-anastomosis plication ileal bypass (SAPI), for the treatment of morbid obesity. Materials and Methods: Totally, 5 female patients with morbid obesity underwent SAPI procedure. The procedure consisted of 2 steps; the first step involved greater curvature plication done in a standardized manner, and the second step involved performing a stapled side-to-side anastomosis between an ileal loop 300 cm distal to the duodenojejunal junction and the gastric antrum. Body mass index (BMI) and percentage excess weight loss (%EWL) at 4 months postoperatively were measured. Results: The median age of patients was 38 years. The mean preoperative BMI decreased from 47.3±7.1 kg/m 2 to 36.3±6.1 at 4 months, postoperatively. The mean %EWL at 4 months after SAPI was 51.5±10.8. The mean operation time was 66±5.47 minutes. The median hospital stay was one day. No postoperative complications were recorded. Conclusions: Despite the small numbers included, the preliminary results of this report show that SAPI is a promising bariatric procedure that achieved significant decrease in BMI and satisfactory excess weight loss. Long-term follow-up of larger number of patients is necessary to reach more firm conclusions on the efficacy and safety of this novel technique. Abstract : Supplemental Digital Content is available in the text.